Attending Night School: Leadership lessons at the Jack Reacher Academy. (8th May 2019) - Bathurst, Ralph; Chrystall, Andrew
Abstract: Night School is the 21st novel by Lee Child featuring the action hero Jack Reacher. As the title suggests, the novel performs a didactic function via an organizational comedy. By invoking James Joyce's Ulysses and his use of double plots, we focus our attention on Reacher as a model leader who occupies a middle space between extremes. He rejects type-set mechanistic responses to problems and navigates around the confusion raised through information overload. Reacher's leadership is enacted on the ground and in the moment, taking each new encounter as an opportunity to learn. His style, marked by a healthy distrust of authority and documents, an ability to follow the spirit of the law and staying flexible are all characteristic of a man who is continually aware of his environment, and not side-tracked by metaphysical constructs. The novel's denouement presents an assessment of both Reacher's and our learning.